Professional Development of Teachers: Obstacles and Suggestions - Ertuğ Can (Anı Publishing, 2019)
In order to improve the quality in education, it is important to determine the obstacles on the way of professional development of teachers and develop suggestions to remove these obstacles. The aim of this research is to determine the obstacles on the way of teachers' professional development and develop suggestions accordingly. Data of the research was gathered from 24 participants via open-ended questions with the answers written. The data were analyzed via qualitative research methods using content analysis. According to the views of the teachers and the administrators, the obstacles for teachers' professional development are based on legal, pedagogical, executive and social reasons. Especially the insufficiency of selection, emplacement and employment of teachers, uncertainty of educational politics, perpetual change of education system, insufficiency of teachers' organizations and teachers' lack of a goal and motivation are viewed as the obstacles for teachers' professional development. According to the results, the following can be suggested in order to remove the obstacles for teachers' professional development: regulation in teachers' selection, emplacement and employment, promotion of educational policies and schedules supporting teachers' professional development, formation of a healthy career planning system, providing learning oppurtunities for a life time and management of every change in education as a governmental policy.